THE ANALYSYS OF THE EFFECTIVENESS OF ADVERTISEMENT TAX REVENUE AND ITS CONTRIBUTION TO THE OWN-SOURCE REVENUE MANADO CITY - Lam, Novita; Sabijono, Harijanto (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Own-source revenue (PAD) is a source of local revenue that can be used freely by each region to organize the administration and regional development. The revenues derive from local tax levies, levies, separated regional wealth management and other income. Advertisement tax is included in the tax area. Advertising Tax is one potential source of tax revenue for the treasury in providing local and contributions given advertisement tax could spur economic development in the city of Manado. The purpose of this study is to determine the level of effectiveness and advertisement tax contribution to Manado own-source revenue. The study was conducted at the Regional Revenue Office of Manado (DISPENDA). The analytical method used is descriptive data analysis from 2010-2014 realization of advertisement tax. The results shows that the effectiveness of the advertisement tax receipts vary widely. The highest level of effectiveness in 2010 amounted to 77.16% and the lowest in 2011 amounted to 63.96%. The overall contribution of advertisement tax in 2010 to 2014 is very less to own-source. The biggest percentage of advertisement tax contribution in 2010 amounted to 2.69% and the lowest in 2014 at 1.24%. DISPENDA management should improve its data collection activities or registration of existing potential sources of tax and the collection of deposit which have not been paid when there is extension or billboards installation (payment in arrears). Keywords: revenue areas, effectiveness, contributions